2007
DOI: 10.1177/154405910708600206
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Posterior Crossbite is Not Associated with TMJ Clicking in Young Adolescents

Abstract: Unilateral posterior crossbite has been considered as a risk factor for temporomandibular joint clicking, with conflicting findings. The aim of this study was to investigate a possible association between unilateral posterior crossbite and temporomandibular disk displacement with reduction, by means of a survey carried out in young adolescents recruited from three schools. The sample included 1291 participants (708 males and 583 females) with a mean age of 12.3 yrs (range, 10.1-16.1 yrs), who underwent an orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
3
26
0
3
Order By: Relevance
“…However, the results from the present survey must be interpreted with caution due to the restricted group of subjects presenting open bite. Among different malocclusions, posterior cross‐bite is thought to have a strong impact on the correct functioning of the masticatory system . In accordance with the current findings, previous studies revealed an association between posterior cross‐bite and TMD signs and symptoms .…”
Section: Discussionsupporting
confidence: 92%
“…However, the results from the present survey must be interpreted with caution due to the restricted group of subjects presenting open bite. Among different malocclusions, posterior cross‐bite is thought to have a strong impact on the correct functioning of the masticatory system . In accordance with the current findings, previous studies revealed an association between posterior cross‐bite and TMD signs and symptoms .…”
Section: Discussionsupporting
confidence: 92%
“…However, it must be stressed that a correct diagnosis of posterior cross‐bite was performed in the first investigation , because the sample was recruited directly in the secondary schools and underwent clinical examinations. Furthermore, the accuracy of self‐reported TMJ clicking assessed at baseline considering objective TMJ clicking as gold standard showed high specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also found no associations or very weak associations between temporomandibular disorders and malocclusion traits. [13][14][15][16] There are only a few reports in the literature regarding the association between occlusal curvatures and the incidence of TMDs. The curves of Spee and Wilson are both of high significance in the establishment of a balanced and functional occlusion, 17,18 which provides bilateral, simultaneous, and equal contacts.…”
Section: Introductionmentioning
confidence: 99%